The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/tropicalmed8020081
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Conspiracy Beliefs of Healthcare Workers in Lebanon towards Monkeypox

Abstract: The emergence of a monkeypox (MPOX) outbreak in 2022 represented the most recent recognizable public health emergency at a global level. Improving knowledge and attitude towards MPOX, particularly among healthcare workers (HCWs), can be a valuable approach in public health preventive efforts aiming to halt MPOX virus spread. The aim of the current study was to evaluate the knowledge and attitude of HCWs in Lebanon towards MPOX and to assess their conspiratorial attitude towards emerging virus infections (EVIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 72 publications
5
25
2
Order By: Relevance
“…However, an early report by the WHO revealed that a lack of knowledge regarding mpox, particularly among healthcare providers, can be a major barrier to the preventive efforts [ 24 ]. Previous studies have found that the knowledge level about mpox is relatively low among health professionals and students as well as among the public in various regions of world, including the Middle East [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In the first month following the WHO alert, public concern over COVID-19 outpaced that of mpox in some countries outside Africa [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, an early report by the WHO revealed that a lack of knowledge regarding mpox, particularly among healthcare providers, can be a major barrier to the preventive efforts [ 24 ]. Previous studies have found that the knowledge level about mpox is relatively low among health professionals and students as well as among the public in various regions of world, including the Middle East [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In the first month following the WHO alert, public concern over COVID-19 outpaced that of mpox in some countries outside Africa [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCWs play a signi cant role in managing and lessening the effects of Mpox epidemics, which is at the heart of these essential elements [15][16][17][18][19][20][21][22][23][24]. The relevance of HCWs' KAP towards Mpox and the need for thorough education and training programs has not been stressed enough if one analyses the literature on this subject [9][10][11]. To effectively prevent and prepare for future outbreaks, health workers' knowledge and attitudes about the Mpox outbreak response, prevention, and readiness must be improved [27].…”
Section: Meta-analytical Resultsmentioning
confidence: 99%
“…Nations must provide healthcare workers with education and training as a top priority as the Mpox epidemic landscape changes so that they are prepared to handle potential cases and successfully support outbreak response operations [29][30][31]. Governments and health organizations can improve their overall readiness and response capacities and protect public health on a global scale by promoting a holistic strategy for Mpox education [9][10][11][12].…”
Section: Meta-analytical Resultsmentioning
confidence: 99%
“…Second, the context of Mpox vaccination intention assessment in terms of place and time should be taken into account. The current study was conducted following the COVID-19 pandemic, which was accompanied by high rates of vaccination hesitancy linked to misinformation and various conspiratorial ideas that were widely prevalent in Jordan, even among health professionals [ 39 , 44 , 45 , 65 , 90 ]. Thus, a spillover of these conspiratorial ideas into the Mpox outbreak is an expected outcome and should be further investigated, considering its potential link with negative health-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%